Efek Usia dan Tingkat Pendidikan terhadap Kinerja Tenaga Bantu Penyuluh Pertanian - Danang Sudarso Widya Prakoso Joyo Widakdo; Abdul Holik; Lutfi Nur Iska (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2021)
The purpose of this study was to determine the effect of age and level of education on the performance of agricultural extension assistants, either simultaneously or partially. This research is an explanatory study with a quantitative approach. The sample of the research was the Agricultural Extension Assistants in Banyuwangi Regency. The sampling technique was a total sampling of 40 respondents. The main data of this research are primary data obtained by data collection techniques using a questionnaire. The analytical tool used multiple linear regression to determine the effect simultaneously and partially. The results showed that age and education level had a positive and significant effect on the performance of agricultural extension assistants, either simultaneously or partially.